Busana Casual dan Gaun Pesta Malam Inspirasi Bunga Rafflesia Arnoldii - Farli, Vina Febria; Kencana, Mega; Surya, Wirma (Style : Journal of Fashion Design, 2023)
The work report entitled "Casual Clothing and Evening Party Dresses Inspired by Rafflesia Arnoldii Flowers" in the form of casual clothes and evening party dresses. Casual clothing means relaxed and simple where this clothing is worn in everyday life and in informal events. Evening party dress clothing is clothing that is used on the occasion of a party event at night. This fashion work was inspired by the Rafflesia Arnoldii flower. The Rafflesia Arnoldii flower, the largest flower, reaches 70 to 110 in diameter with a height of 50 cm consisting of five large, thick and leathery petals which are orange and maroon in color, with white irregular spots, stamens, sharp and thin in the middle hole. flower. Making casual clothes and evening party dresses through a process of preparation, design and implementation. Using bridal satin, basurek, balotelli batik, velvet satin, hero, Swarovski pearl tille, and sand / crinkle organza. The works created are clothing, Rafflesia Arnoldii casual 1, Rafflesia Arnoldii 2, Rafflesia Arnoldii casual 3, Rafflesia Arnoldii party dress